Trends in the Non-Performing Assets of State Bank of India and its Associates - Jayachandran, R.; Nagananthi, T. (Indian Journal of Finance, 2008)
The public sector banks dominate the Indian banking sector. They have 82 percent market share in the total deposits and advances of the industry. But when it comes to efficient non-performing assets management and innovative strategies for growth, foreign banks and even the private banks have an upper hand. The size of deposits, advances and the branch network are the tools to assess a good bank. Non-performing assets and excess staff are some of the banes of the banking sector.